Cardiac Energetics in Patients With Aortic Stenosis and Preserved Versus Reduced Ejection Fraction. Issue 24 (16th June 2020) - Peterzan, Mark A.; Clarke, William T.; Lygate, Craig A.; Lake, Hannah A.; Lau, Justin Y.C.; Miller, Jack J.; Johnson, Errin; Rayner, Jennifer J.; Hundertmark, Moritz J.; Sayeed, Rana; Petrou, Mario; Krasopoulos, George; et al.
Abstract : Background: Why some but not all patients with severe aortic stenosis (SevAS) develop otherwise unexplained reduced systolic function is unclear. We investigate the hypothesis that reduced creatine kinase (CK) capacity and flux is associated with this transition. Methods: We recruited 102 participants to 5 groups: moderate aortic stenosis (ModAS) (n=13), SevAS, left ventricular (LV) ejection fraction ≥55% (SevAS-preserved ejection fraction, n=37), SevAS, LV ejection fraction <55% (SevAS-reduced ejection fraction, n=15), healthy volunteers with nonhypertrophied hearts with normal systolic function (normal healthy volunteer, n=30), and patients with nonhypertrophied, non–pressure-loaded hearts with normal systolic function undergoing cardiac surgery and donating LV biopsy (non–pressure-loaded heart biopsy, n=7). All underwent cardiac magnetic resonance imaging and 31 P magnetic resonance spectroscopy for myocardial energetics. LV biopsies (AS and non–pressure-loaded heart biopsy) were analyzed for CK total activity, CK isoforms, citrate synthase activity, and total creatine. Mitochondria-sarcomere diffusion distances were calculated by using serial block-face scanning electron microscopy. Results: In the absence of failure, CK flux was lower in the presence of AS (by 32%, P =0.04), driven primarily by reduction in phosphocreatine/ATP (by 17%, P <0.001), with CK k f unchanged ( P =0.46). Although lowest in the SevAS-reduced ejection fraction group, CK flux was not different from the SevAS-preserved ejection fraction group ( P >0.99). Accompanying the fall in CK flux, total CK and citrate synthase activities and the absolute activities of mitochondrial-type CK and CK-MM isoforms were also lower ( P <0.02, all analyses). Median mitochondria-sarcomere diffusion distances correlated well with CK total activity ( r =0.86, P =0.003). Conclusions: Total CK capacity is reduced in SevAS, with median values lowest in those with systolic failure, consistent with reduced energy supply reserve. Despite this, in vivo magnetic resonance spectroscopy measures of resting CK flux suggest that ATP delivery is reduced earlier, at the moderate AS stage, where LV function remains preserved. These findings show that significant energetic impairment is already established in moderate AS and suggest that a fall in CK flux is not by itself a necessary cause of transition to systolic failure. However, because ATP demands increase with AS severity, this could increase susceptibility to systolic failure. As such, targeting CK capacity and flux may be a therapeutic strategy to prevent and treat systolic failure in AS. Abstract : Supplemental Digital Content is available in the text.